Modelagem cinemática e Dinâmica de uma estrutura RRP+PR - Díaz, Jorge Eliécer Rangel (2011)
The aim of this work is to develop a non-contact 3D scanning robot to measure surfaces from objects of small sizes. The 3D scanner is shaped for a mechanical structure and an optic lecture system. The mechanical structure has 5 degrees of freedom. Such system is composed by two kinematic chains used to move the laser sensor and the workpiece respectively. The lecture system is derived from a laser sensor, based on 3D active triangulation technique that acquires the surface workpiece data. This technique assurance the scanning of the workpiece surface with reduced dimensional errors and consequently it makes possible the use less data points. Therefore it is achievable the fast data processing to reverse engineering method. In order to analyze its kinematics and dynamic model, its workspace, error analysis, and efforts at the joints, methods for reading the surface coordinates were proposed. For the analysis were considered the resolution and mechanical characteristics of the components used for the construction of a prototype.